Avoin vai suljettu yhteisö - johtaminen seurakunnassa: tiivistelmä tutkimushankkeesta Suomen ev.-lut. seurakunnat työntekijäyhteisönä - Palmu, Harri (Kirkon Tutkimuskeskus / B, 1990)
Engl. Zsfassung u.d.T.: The community as a closed or an open system - leadership in the parish : a summary of the study project of Lutheran parishes in Finland as working communities